KARAKTERISTIK PASTA BAWANG MERAH (Allium ascalonicum L.) BERDASARKAN PERBEDAAN SISTEM EMULSI - Nuraisyah, Anni; Rodiahwati, Wawat; Isworo, Rhestu Isworo; Mikhratunnisa (Jurnal TAMBORA, 2021)
Bima Regency has great potential in producing shallots (Alliumascalonicum L.) because it can be planted throughout the year so that the production is abundantRed onion. Onion processing aims to maintain agesave and the quality of the onion. This study compared the characteristics of the pastashallots with two different emulsifying systems. Use of an emulsion systemthe right one affects the quality of the shallot paste. The research was conducted in a scalelaboratory using a completely randomized design (CRD) with two treatments andthree replications, the first treatment was addition of shortening with lecithin, andthe second treatment adding starch with oil palm. Characteristics of onion pastered that want to be investigated are water content (AOAC 2005), protein content (AOAC, 2005) andfat content (AOAC, 2005). The test results of shallot paste show thatThe addition of CMC 0.3% for 7 minutes had the lowest water content (44.11%).While the addition of 6% lecithin 4 minutes has a higher water contentcompared to other treatments (51.27%). The highest protein content is found intreatment with the addition of CMC 0.3% 7 minutes is 3.05%. while lowest onlecithin addition treatment 6% 4 minutes is 2.63%. Fat content of shallot pasteThe highest was the treatment with the addition of CMC by 0.3% with timestirring 7 minutes (0.89%), while the lowest was found in treatment withaddition of 6% lecithin with a stirring time of 4 minutes (0.82%).